Broiler walking ability and toe asymmetry under harsh rearing conditions - Baracho, MS; Nääs, IA; Bueno, LGF [UNESP]; Nascimento, GR; Moura, DJ (Fundação APINCO de Ciência e Tecnologia Avícolas, 2012)
Morphological asymmetry has been described as a potential broiler welfare indicator, for interpreting the birds' ability to cope with the challenges that may affect its growth. The objective of this study was to evaluate the use of morphological asymmetry data to estimate broiler walking ability and welfare.dBroilers werefed diets supplemented or not with vitamin D. Toes were measured when birds were 42 and 49 days old using digital caliper.the left and right sides of the following four bilateral traits (tarsometatarsus length, outer toe length, mid toe length, and back toe length) were measured twice on intact alive birds by two different researcherh. Data from right and left sides were compared in the two treatments using the Student t-test, and Pearson's correlation was used to analyze the total asymmetry found as a result of the total sum of the differences in the measurements. Asymmetry data were comparedwith the total numberof leg lesions. Mid toe and tarsometatarsus asymmetry resultswere considered as actual fluctuating asymmetry, and presented normal distribution (Test of Kolmogorov-Smirnov, p >0.05). However, back toe and outer toe measurements were not normally distributed, as determined by the test of Kolmogorov-Smirnov (p <0.05), indicating anti-asymmetry; when comparing right with left limb,results were significantly different fron zero (t-Student, p <0.05) indicating directional fluctuating asymmetry.The welfare of broilers withwalking difficulty due to the presence of severe asymmetry in limbs is poor.
Keywords: Asymmetry; welfare; poultry